Higher prevalence of NUDT15 rs116855232 compared to TPMT rs1142345 in a Chinese cohort and its implications for thiopurine therapy - Zhao, Chenyu; Huang, Hui (Frontiers in Pharmacology, 2025)
BackgroundThiopurine drugs are widely used as immunosuppressants and chemotherapeutic agents in clinical practice, but their adverse effects significantly limit their clinical application. TPMT c.719A>G (rs1142345) and NUDT15 c.415C>T (rs116855232) are the most common genetic polymorphisms influencing thiopurine drug toxicity, with notable differences in allele frequencies across diverse populations. However, there remains a paucity of research on the NUDT15 c.415C>T polymorphism in the Chinese population.MethodsThis study enrolled 571 Chinese patients. DNA samples were isolated, and polymerase chain reaction (PCR) was performed to amplify the TPMT c.719A>G and NUDT15 c.415C>T in each sample. PCR products were genotyped via Sanger sequencing to identify the allelic frequencies of these polymorphisms. Additionally, we compared the detection rate of NUDT15 c.415C>T and TPMT c.719A>G for thiopurine drug toxicity in the cohort.ResultsThe minor allele frequencies of NUDT15 c.415C>T and TPMT c.719A>G were determined to be 12.52% and 2.36%, respectively. The detection rate of the NUDT15 c.415C>T polymorphism was significantly higher than that of TPMT c.719A>G (23.47% vs. 4.55%, P < 0.001).ConclusionNUDT15 c.415C>T yielded a higher carrier rate than TPMT c.719A>G in this cohort. And broader panels could shift absolute yields. These findings highlight the critical role of NUDT15 c.415C>T genotyping in guiding precision therapy with thiopurine drugs.